Cross-cultural adaptation of an anxiety measure in a disadvantaged South African community context: Methodological processes and findings. (December 2021) - Myburgh, Naomi; Loxton, Helene; Engels, Rutger C.M.E.
An important challenge to enhancing community access to mental health interventions in marginalised, transcultural settings is the development of culturally relevant screening measures. Cross-cultural adaptation (CCA) and translation methods offer guidelines for the adaption of existing screening measures for use across cultures with the aim of preserving semantic and construct equivalence as well as validity. Yet, the application of CCA methods has been inconsistent and validation strategies have focused predominantly on expert review and quantitative validity testing. Additionally, potentially important context-specific interpretations of measure items have been lost in translation-heavy approaches. The missing link in the CCA of existing measures may be the addition of culturally sensitive, community-based evaluative methods. This paper presents a report of the application of a seven-step CCA method developed by the first author to address the issue of cultural relevance in the translation and cross-cultural adaptation of the Spence Child Anxiety Scale (SCAS) an anxiety measure for use in a specific South African community context. The findings emphasise the surprising context-specific interpretations of items in measures applied transculturally, which support the case for qualitative, community-based validation of translated, CCA screening measures used to explore the effectiveness of mental health interventions across cultural contexts.